Desenvolvimento de massas congeladas de pães tipo forma contendo ingredientes funcionais - Zambelli, Rafael Audino (2014)
The aim of this study was to develop formulations of breads type processed form with functional ingredients polydextrose, tomatoes, broccoli and acai powder and study its getting through the frozen mass technology, evaluating the effect of frozen storage for 60 days in quality parameters breads. It was applied three a central composite design (CCRD) for the development of formulations. Three combinations of ingredients were used: polydextrose and broccoli powder, tomato powder and polydextrose polydextrose and acai powder, and these independent variables incorporated at levels of 0-20 % (flour basis). The CCRD included eleven trials : four factorial points , four axial and three replicates at the center point. The results of the CCRD were analyzed by Response Surface Methodology (RSM), with the response variable the factor of maximum expansion of the masses, specific volume, density and rate of expansion of the loaves. Two trials of each combination of ingredients , which achieved the best results with respect to these parameters were chosen for the study of obtaining the frozen dough technology. The effect of frozen storage period (0, 15, 30, 45 and 60 days) was evaluated through the average data values of the quality characteristics of bread, which we assessed the factor of expansion and production volume of the masses as well as the specific volume, density, expansion ratio, pH, acidity, colorimetry, crumb structure, texture profile analysis (TPA) and sensory analysis. For statistical analysis we used variance analysis, Tukey test and regression analysis was applied. The results showed that the incorporation of the functional parameters altered ingredients maximum expansion factor , specific volume, density, and expansion ratio of the loaves, damaging them in quantities up to 30 g. The study of obtaining frozen dough was held for seven formulations (standard, without adding functional ingredients , T1 and T2, with 5 to 10% polydextrose and tomato powder, respectively, B1 and B2, 5 to 10%, polydextrose and broccoli powder and A1 and A2, containing 5% to 10% polydextrose and acai powder. Generally, the time for frozen storage promoted the reduction of viable yeast cells, this reduction was less with the bread functional ingredients that have preserved greater number of cells after 60 days of frozen storage as compared to standard formulation. frozen storage expansion factor reduced the production volume and the mass and the specific volume expansion ratio and breads and enhanced density. was increased brightness of the loaves with functional ingredients and reduced chromaticity. Total moisture content of the mass showed a significant reduction (p≤0.05), and the number of alveoli and its circularity. Was increased the area and perimeter. For texture parameters, there was an increase in hardness, gumminess, chewiness and cohesiveness, which influenced the decrease of sensory attributes as a function of storage time. was concluded that the time of frozen storage was damaging the quality of breads however, this harmful effect was smaller breads incorporated with functional ingredients, due to greater preservation of viable yeast cells.